Multiple phases in regulation of Nanog expression during pre‐implantation development. (14th December 2015) - Komatsu, Kouji; Fujimori, Toshihiko
Abstract : Nanog is a key transcriptional factor for the maintenance of pluripotency of ES cells, iPS cells or cells in early mammalian embryos. The expression of Nanog is mainly localized to the epiblast in the late blastocyst. The Nanog gene expression pattern varies between embryos and between blastomeres during blastocyst formation. In this report, we traced the changes of Nanog expression in each cell in developing preimplantation mouse embryos through time‐lapse observation of Nanog‐GFP transgenic mouse embryos. The expression pattern of Nanog was classified into four phases depending on the developmental stage. Nanog expression started at very low levels during cleavage stages. It increased stochastically during the morula stage, but its expression level had no clear correlation with future cell fates. After the 32‐cell stage, when embryos form the blastocyst cavity, Nanog expression was upregulated mainly in ICM cells while it was repressed in the future primitive endoderm lineage in an FGF signaling‐dependent manner in the later stages. These results indicate that there are multiple phases in the transcriptional regulation of Nanog during blastocyst formation. Abstract : The changes of expression of Nanog gene, a pluritpotency related gene, in each cell in developing preimplantation mouse embryos were analyzed by the timelapse observation of Nanog‐GFP transgenic mouse embryos. It was suggested that there are multiple phases in the regulations of Nanog expression during blastocyst formation.